2021
DOI: 10.1007/s00784-021-03835-6
|View full text |Cite
|
Sign up to set email alerts
|

Dental and periodontal disease in patients with inflammatory bowel disease

Abstract: Objectives Although bowel symptoms are often predominant, inflammatory bowel disease (IBD) patients can have several oral manifestations. The aim of this study was to investigate the prevalence of dental caries and periodontal disease in patients with Crohn’s disease (CD) and ulcerative colitis (UC) compared to an age and gender-matched control group of patients without IBD. Material and methods The DMFT (Decayed, Missing, Filled Teeth) scores and the DPSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
5
23
0
2
Order By: Relevance
“…In contrast, Schütz et al [29] noticed that in CD patients, caries prevalence was increased by a longer disease duration but depended on insufficient oral hygiene and intensified sugar consumption. Tan et al [32] observed a significant increase in the DMF-t index only in the CD group but not in the UC group, while the periodontal status did not differ between IBD patients and healthy subjects.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, Schütz et al [29] noticed that in CD patients, caries prevalence was increased by a longer disease duration but depended on insufficient oral hygiene and intensified sugar consumption. Tan et al [32] observed a significant increase in the DMF-t index only in the CD group but not in the UC group, while the periodontal status did not differ between IBD patients and healthy subjects.…”
Section: Discussionmentioning
confidence: 92%
“…In a retrospective study, 229 IBD patients were compared with 135 healthy subjects regarding DPSI (Dutch PSI) and DMFT. While DMFT was significantly higher in IBD patients than in healthy subjects, DPSI did not differ between the groups regarding specific IBD medications (30). Other studies compared 99 CD patients and 80 UC patients with 74 periodontitis patients according to the DMFT, BOP, PD and plaque index parameters.…”
Section: Discussionmentioning
confidence: 92%
“…We know from the previous literature that some of the same cytokines are involved in IBD and P pathogenesis and that these cytokines are detectable outside the gut, namely, in the oral cavity (14)(15)(16)(17). In this context, many studies have already described altered parameters in the periodontium, in particular, elevated periodontal parameters in IBD patients (4,13,30).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study show a significantly higher prevalence of RFT in patients with IBD (3.2 ± 2.6) compared to healthy control patients (0.9 ± 1.3; p < .01). This finding could be explained, at least in part, by the higher incident of caries, the main cause of AP, in patients with IBD (Koutsochristou et al, 2015; Nijakowski et al, 2021; Tan et al, 2021; Zhang et al, 2020). A recent systematic review has highlighted a remarkably increased past and present occurrence of dental caries in subjects with IBD, compared to healthy controls (Marruganti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%